Peningkatan Kualitas Green Bean Melalui Teknik Fermentasi Dan Pemanfaatan Limbah Kopi Untuk Produksi Kompos di Desa Sajang, Sembalun, Lombok Timur - Fuadi, Mi’raj; Kurniawan Yuniarto; Sella Antesty; Yuhendra AP; M. Azhar Mustafid; Mutia Devi Ariyana; Wenny Amaliah; Yessica Romauli Sinaga; Nur Afni; Made Gendhis Putri Pertiwi; Wiwin Apriyanditra; Pavalee Chompoorat Tridtitanakiat (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
Coffee is one of the leading agricultural products in Indonesia, including the West Nusa Tenggara (NTB) region, which is known for its high quality coffee production. Sembalun sub-district, especially Sajang, has great potential in developing arabica coffee that can compete in the international market. However, the challenges faced by coffee farmers are still quite significant, especially in improving the quality of coffee fruit and managing coffee waste more effectively. The implementation of collaborative international community service (PkM) in Sajang related to improving coffee quality has many significant benefits, especially in women's empowerment, sustainable agriculture, and economic potential. International collaborative community service involves various stakeholders, both from within and outside the country, to solve problems efficiently and solutively, especially in sustainable agriculture issues. The focus of this PkM is to educate and equip the community, with the latest innovations and technologies to improve the quality of local coffee. The workshop went well, involving village officials, 20 members of Bumi Lestari Indonesia farmers (male and female) and coffee business owners.